Design of license plate recognition system based on capsule network. Issue 1 (July 2020) - Guan, Tian; Zhen, Yajing; Song, Xiaoli; Liu, Jiawei; Wang, Mengen; Wang, Zhaojian; Zhang, Yaoming; Zhang, Dongsheng
Abstract: With the development of automobile industry, the license plate, as the unique identifier of the vehicle, plays an important role in vehicle management. License plate recognition technology is mainly realized by image processing technology. It mainly includes image preprocessing, license plate positioning, character segmentation and other processes. In the actual process of license plate recognition, it is often impossible to accurately recognize the license plate due to the positional relationship such as angle. Therefore, this paper proposes a license plate recognition program based on the capsule network. First, through image preprocessing, license plate positioning, and character segmentation, and then use capsule neural network for training and simulation in order to achieve the object of accurate character recognition.